2016
DOI: 10.1016/j.amepre.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Improving Sickle Cell Transitions of Care Through Health Information Technology

Abstract: The environmental scan did not reveal an existing suitable transition tool, but patients, parents, providers, and IT experts saw the potential and appeal of creating a tool to meet ED health information needs to improve care transitions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…A recent study developed in the United States reaffirmed the importance of family members being present in patient care, during all stages of life relative to sickle cell disease, from childhood, youth to the transition to adulthood. In addition, he pointed out that these people have also used virtual technologies to search for data on the symptoms of this disease, among other information, which worries health professionals because they consider inaccurate data shared on the internet (24) .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study developed in the United States reaffirmed the importance of family members being present in patient care, during all stages of life relative to sickle cell disease, from childhood, youth to the transition to adulthood. In addition, he pointed out that these people have also used virtual technologies to search for data on the symptoms of this disease, among other information, which worries health professionals because they consider inaccurate data shared on the internet (24) .…”
Section: Discussionmentioning
confidence: 99%
“…For aging survivors, delivery of care is complicated by the need to transition not only from treatment to survivorship and/or primary care but also from pediatric to adult providers. The importance of an effective transition of care has been recognized and is under active investigation in other pediatric chronic conditions, such as sickle cell and congenital heart disease . Within general pediatrics, some have suggested that beginning the process early, engaging the child in medical decision making, and maintaining health insurance are important factors in this transition .…”
Section: Screening Guidelines and Delivery Of Carementioning
confidence: 99%
“…To that end, this paper sets out to understand the knowledge creation practices in the care of sickle cell disorder, which remains one of the most neglected genetic disorder having severe implications for maternal, newborn and child health in native communities globally (McGann et al, 2016;Singh et al, 2019;Ware, 2013). Health care systems, which provide care for sickle cell disorder in developed economies, have emphasized the role of information and communication technology (ICT) based practices for an effective transition between different care services within the hospital premise (Frost et al, 2016). However, in emerging economies, this disorder continues to prevail among the marginal communities where institutional provisions of care remain constrained due to socio-economic, cultural and clinical factors (High-Level Committee Report, 2014).…”
Section: Introductionmentioning
confidence: 99%